(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
We propose in this article make an approach to gender issues and theThis article is about the ways women define citizenship. For this work, 14 interviews to women from La Pampa who receive the Asignación Universal por Hijo para la Protección Social (AUH) were used. Citizenship is a widely used term in the social sciences to describe the complex processes of inclusion/exclusion. This article attempts to rethink those definitions based on the voices of women from La Pampa Province.